PGE MINERAL FORMATION AND THE STRUCTURE OF THE SYUM-KEU MASSIF (POLAR URALS) - Gurskaya L.I.; Smelova L.V. (My University, 2003)
Data on the PGE-bearing potential of the Syum-Keu massif (Polar Urals) were obtained for the first time. Two types of PGE mineralization, associated with chromite ores and sulfide occurrences, were established. The following three mineral assemblages were distinguished in chromite ores: (1) Ir-Os-Ru (erlichmanite-laurite) in highly magnesian chromite ores (Σ PGE, 0.3 g/t); (2) Ir-Os-Ru-Pt (sperrylite-irarsite-laurite) in aluminous chromite ores enriched with sulfides (Σ PGE, 0.4-0.7 g/t); and (3) proper Pt (ferroplatinum) in coarse recrystallized dunites with poorly impregnated highly ferruginous chromites (Σ PGE reaches 6.5 g/t). A Pt-Pd (mayakite-sperrylite) assemblage associated with pyroxenites is abundant in sulfide ores (Σ PGE reaches 1.2 g/t).